2016
DOI: 10.1667/rr14463.1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Radiation Response in Breast Cancer Stem Cells by Inhibition of Thioredoxin- and Glutathione-Dependent Metabolism

Abstract: The current study determined if depletion of glutathione (GSH) and inhibition of thioredoxin reductase (TR) activity could enhance radiation responses in human breast cancer stem cells by a mechanism involving thiol dependent oxidative stress. Buthionine sulfoximine (BSO), a GSH synthesis inhibitor; sulfasalazine (SSZ), an inhibitor of xc- cysteine/glutamate antiporter; auranofin (Au), a thioredoxin reductase inhibitor; or 2AAPA, a GSH-reductase inhibitor, were used to inhibit GSH- and thioredoxin (Trx)-metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 25 publications
(48 reference statements)
5
90
0
Order By: Relevance
“…The combination AF plus BSO showed a preferential radiosensitizing effect in hypoxic tumor cells, which featured an impaired radioresponse in the TMCS, our model of metabolic hypoxia. In mice, their simultaneous administration enhanced radioresponse in EMT6 and 4T1 mammary carcinomas, in line with a very recent report in a MDA-MB-231 breast cancer model [20]. We concluded that the combination of AF and BSO could be a promising radiosensitizing strategy justified in view of them being ready-to-use pharmaceuticals for clinical evaluation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The combination AF plus BSO showed a preferential radiosensitizing effect in hypoxic tumor cells, which featured an impaired radioresponse in the TMCS, our model of metabolic hypoxia. In mice, their simultaneous administration enhanced radioresponse in EMT6 and 4T1 mammary carcinomas, in line with a very recent report in a MDA-MB-231 breast cancer model [20]. We concluded that the combination of AF and BSO could be a promising radiosensitizing strategy justified in view of them being ready-to-use pharmaceuticals for clinical evaluation.…”
Section: Discussionsupporting
confidence: 88%
“…Along with improved radiation responses, AF sensitized breast cancer stem cells, and in combination with BSO decreased cell migration and invasion [20]. Of note, inhibition of TrxR by curcumin and 1, 2, 5-selenadiazole showed a comparable array of antitumor effects including radiosensitization [32, 4547], while the disruption of GSH pathways by genistein and gadolinium (III) texaphyrin resulted in ROS-mediated radiosensitization [48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…TXN1 overexpression in NSCLC is indicative of a more aggressive tumor phenotype, which in turn is associated with bad prognostic features and a poorer outcome . Inhibiting the expression and function of TXN1 has been shown to increase the radiosensitivity of various cancer types …”
Section: Discussionmentioning
confidence: 99%
“…One such difference is alterations in oxidative metabolism that have been noted in cancer versus normal cells [4, 31, 32] as well as cancer stem cells [33]. We have recently published data demonstrating that disruption of redox balance radiosensitizes breast cancer stem cells [34]. Cancer cells appear to demonstrate both increased steady state levels of ROS (O 2 •- and H 2 O 2 ) and abnormal metabolism of transition metals when compared to normal cells [4, 35].…”
Section: Discussionmentioning
confidence: 99%